Die another day: duration in German import trade - Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2007)
International trade patterns at the product level are surprisingly dynamic. The majority of trade relationships exist for just a few, often only one to three, years. In this paper, I examine empirically the duration in German import trade at the 8-digit product level from 1995 to 2005. I find that survival probabilities are affected by exporter characteristics, product type and market structure. Specifically, I show that the duration of exporting a product to Germany is longer for products obtained from countries that are economically large and geographically close to Germany; for products with large trade value and a low elasticity of substitution; and for trade pairs that command a large share of the German import market and are characterized by two-way trade.
Keywords: F14; F19; C14; C41; 330; Import; Produkt; Internationale Wirtschaftsbeziehungen; Dauer; Außenhandelsstruktur; Deutschland